Reproductive health in the Americas - Omran, Abdel R... [et al] ed. (PAHO WashingtonUS, 1992)
Describes for the Americas the various reproductive patterns. Evaluates the impact on health of family formation patterns and changing attitudes toward reproduction. Provides up-to-date accounts of fertility regulation and displays the existing experiences in reproductive health. Identifies unmet needs in service and research in these areas, and suggests strategies for filling the gaps. Focuses on adolescent pregnancy in Latin America and the English speaking Caribbean.